2006 IEEE International Conference on Robotics and Biomimetics 2006
DOI: 10.1109/robio.2006.340255
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Control of the Hydraulic Shoulder A 3-DOF Parallel Manipulator

Abstract: -In this paper, a model-based impedance control strategy is developed for a 3 DOF parallel manipulator to manage the interaction of the robot with the environment. Kinematic and dynamic modeling of the manipulator has been analyzed in order to be used for both simulation and control purposes. The impedance controller objective and the structure of the proposed controller are introduced and controller gain selection is discussed. A simulation study evaluates the effectiveness of the proposed impedance control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A large B d can increase the response time and have no vibration. For position accurate tracking, a large K d should be selected [ 14 ]. According to these, the suitable impedance parameters for specified control system can be got.…”
Section: The Control System Of Tendon-driven Dexterous Fingermentioning
confidence: 99%
“…A large B d can increase the response time and have no vibration. For position accurate tracking, a large K d should be selected [ 14 ]. According to these, the suitable impedance parameters for specified control system can be got.…”
Section: The Control System Of Tendon-driven Dexterous Fingermentioning
confidence: 99%
“…It is typically used in applications that require complex interaction with the environment, such as assembly, drilling, and milling. However, some researches [23,24] have shown that impedance control also demonstrates the desirable trajectory tracking ability in free motion. The tracking ability of impedance control in free motion can be explained by introducing the concept of a virtual surface.…”
Section: Introductionmentioning
confidence: 99%
“…As such, studies on the impedance control of 3-DOF PLMs have covered several subjects, including parts assembly [23], rehabilitation [24], and haptic devices [25]. Redundant actuators have been employed in these studies [24]- [26]. However, the internal force caused by the redundant actuators is of no concern in control algorithms.…”
Section: Introductionmentioning
confidence: 99%